Income Distribution, Market Imperfections and Capital Accumulation in a Developing Economy - Dasgupta, Asim K. (Springer Singapore, 2018)
The book explains the problem of insufficient capital accumulation and growth in a less developed country. In conventional analyses, such explanations are often found exogenised in terms of factors such as socio-cultural attitudes towards saving and investment, irrationality of peasant behaviour, technological aspects of externalities and demographic parameters. This book provides an alternative explanation in terms of distribution of income and assets. Focusing on the agricultural sector of a developing economy, it describes how this approach can be extended to cover the industrial sector as well. Further, it develops a model that is then used to analyse the specific problem of capital accumulation in agriculture.